Bacterial resistance to antibiotics used in treatment of gonorreia: a literature review (Research, Society and Development, 2021)
Gonorrhea is a sexually transmitted infections that is among the most common public health problems worldwide. This disease is caused by the gram-negative bacterium Neisseria gonorrhoeae, which is a microorganism restricted to humans. Since it presents itself as a frequent infection, N. gonorrhoeae shows an extraordinary ability to develop resistance to multiple classes of antibiotics, becoming extremely important, besides worrying public health authorities. Therefore, the objective of this work was to present a survey about the main antibiotics associated with resistance attributed to N. gonorrhoeae, according to scientific publications presented in 2017 and 2018, in different databases (Scielo, PubMed, Lilacs and Google Scholar). Through an integrative literature review, using terms according to the Health Descriptors - DeCS, articles were found based on national and international data that had a close relationship with the proposed theme. They were selected for data analysis and description, thus allowing an understanding of the problem presented. Antibiotic resistance by N. gonorrhoeae strains is found to be widespread worldwide. It is clear that ceftriaxone, cefixime, cefotaxime, penicillins, tetracyclines and macrolide derivatives are no longer effective in treating infections caused by this microorganism. Findings warn of this serious public health problem.